EFEKTIVITAS PENUKAR KALOR TIPE PLATE P41 73TK Di PLTP LAHENDONG UNIT 2 - Harlan Egeten; Frans Palobo Sappu; Benny L Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2014)
One way to keep a plant operate optimally is keeping the effectiveness of the components properly. One of the components used in the production process is heat exchanger. In PLTP Lahendong unit 2 is used as a the cooler lubricant system of generator and turbine is using type of plate P41 73TK heat exchanger.This research objective is to determine the effectiveness of the heat exchanger plate type PLTP Lahendong P41 73TK. Calculation are using formulas that correspond to the type of heat exchanger plate and plate heat exchanger assuming that analyzed as a tube.Results of the calculations shows that the effectiveness of plate heat exchanger on the methods of LMTD is 83,3%, obtained by the thermal heat exchanger effectiveness of 55.6% and effectiveness based on method of NTU is 30.3%.Keywords : Effectiveness, type heat exchanger plate, LMTD method, method of NTU